KRITIK MATAN (Sebuah Upaya Menjaga dan Meneropong Orisinalitas Hadîts) - Arif Wahyudi (Al-Ihkam: Jurnal Hukum dan Pranata Sosial)
Matan critic is a critic that emphasizes to matan that comes from neutral concept or suspicion to the validity of Hadîts from matan perspective. Many controversy of matan critic, such as when this problem is discussed, as soon as it will appear a blasphemy that means it doubts the prophet’s utterance. Although matan critic has been done since the prophet’s friends era by comparing matan of Hadîts with al-Qur’ân or the other Hadîts. They doubted about it even they refused a Hadîts that was considered as contradiction of al-Qur’ân and the other Hadîts told by more capable people. The ulama then covered this matan critic by using the certain theories discussed in the study of Hadîts dirâyah. On the other hand, many people said that matan critic is not perfect and it needs to be functioned well.